Assessment of biosafety precautions in medical laboratory workers, Derna city,Libya - khagkhag, S.; Alhosni, M.; Naser, Tasneem; Ahmed, Shaima; Fareg, Esra; Taher, Amani (International Journal of Psychosocial Rehabilitation, 2020)
Biosafety during lab work is an important concern in developing countries. Some critical issues concerning biosafety are lack of training, exceeding workload, working too fast, deciding not to follow safe practices, and skepticism about biohazards. This study aimed to determine biosafety perception and practices of laboratory technicians during routine work in clinical laboratories of Derna city, Libya. A total of 75 laboratory technicians were interviewed from major public sector laboratories and a few private laboratories throughout Derna city. A total of 28 (37.3%) males and 47(62.7%) females participated in the study, with over half (85.3%) having 2-5 years of work experience. Results showed that 52% of the laboratory technicians from private laboratories. Almost 57.3% of the respondents said they take vaccine against communicable diseases. Results showed that 10 % of the laboratory technicians did not use any personal protective equipment. Furthermore, 30.7% of the respondents said they discard used syringes directly into municipal dustbins. Standard operating procedures were not available in all laboratories. No formal biosafety training had been provided to all of the respondents. Laboratory technicians in Derna city lack awareness of good laboratory practices and biosafety measures, and also face a lack of resources.